PERAN BHABINKAMTIBMAS DALAM MENEKAN TERJADINYA PERNCURIAN KENDARAAN BERMOTOR DI WILAYAH HUKUM POLSEK KARAWANG - Pratama, Kresnayogi (Police Studies Review, 2020)
The problem of motor vehicle theft is a type of crime that always causes disturbance and public order. The large number of migrants to the District of West Karawang and East Karawang has resulted in a high number of criminal acts occurring in the jurisdiction of the Karawang Police Station. Based on data from the Karawang Sector Police, motor vehicle theft is the most crime compared to other crimes. This study aims to describe the role and efforts of Bhabinkamtibmas as well as what factors are hampering the role of Bhabinkamtibmas in suppressing the occurrence of Curanmor in the Karawang Sector Police jurisdiction. The research location is Karawang Police Station, Bhabinkamtibmas Unit. This study uses a qualitative research approach with the Field Research method. Using data triangulation (Moleong; 2006: 330) 3 (three) kinds of techniques, namely observation, interviews, and document studies. This research uses role theory and communication theory as well as the concept of Bhabinkamtibmas and the concept of curanmor. The role of Bhabinkamtibmas which is carried out in suppressing criminal acts of fraud by Bhabinkamtibmas Karawang Police Sector includes sambang, counseling, community development, hospitality and social security. Lack of personnel, around 9 of the 16 personnel who concurrently held positions at the Karawang Sector Police resulted in a less than optimal role of Bhabinkamtibmas. Internal factors that influence the change of leadership, the number of Bhabinkamtibmas members, communication skills, operational vehicles and external factors are the lack of public awareness, late reporting by, and lack of information. Bhabinkamtibmas as the spearhead of the National Police that directly confronts the public must focus on the most criminal problems, namely curanmor and Bhabinkamtibmas in carrying out its efforts are required to have an effect on the community. Keywords: the role of Bhabinkamtibmas, motor vehicle theft.